Predictive power of grit and emotional intelligence on research anxiety experience of students - Eteng-Uket, Stella; Njaka, Rita Chikwem (American Journal of Education and Learning, 2023)
Research anxiety is one critical factor that may hinder the research activities of students, and variables like grit and emotional intelligence are factors that may exert influences on anxiety levels as well as the research performance of students in the tertiary institution. Thus the study looked into the predictive power of grit and emotional intelligence on the research anxiety experience of tertiary education students. It adopted the correlational research design. To direct the study, three null hypotheses and three research questions were developed. The study's population included all 5,765 undergraduate students at the University of Port Harcourt. A sample of 294 was drawn using stratified random sampling. The Research Anxiety Questionnaire, Emotional Intelligence Appraisal, and the Grit Scale were the instruments used. The validity of these tools was guaranteed. The Cronbach alpha method obtained high-reliability coefficients for the three instruments. Data were analyzed using simple and multiple regressions. The result revealed that grit and emotional intelligence independently and jointly significantly predict the research anxiety experience of students in tertiary education. Considering findings, it was suggested that students in tertiary education receive training that focuses on developing both their grit and emotional intelligence. This essential training could help students to become more resilient in the face of challenges and setbacks, as well as better equipped to manage their emotions in high-pressure academic situations.